2000
DOI: 10.1063/1.125694
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution depth profiling in ultrathin Al2O3 films on Si

Abstract: A combination of two complementary depth profiling techniques with sub-nm depth resolution, nuclear resonance profiling and medium energy ion scattering, and cross-sectional high-resolution transmission electron microscopy were used to study compositional and microstructural aspects of ultrathin (sub-10 nm) Al2O3 films on silicon. All three techniques demonstrate uniform continuous films of stoichiometric Al2O3 with abrupt interfaces. These film properties lead to the ability of making metal-oxide semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
204
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(208 citation statements)
references
References 12 publications
4
204
0
Order By: Relevance
“…3 4 using the narrow ͑⌫ =40 eV͒ resonance in the 27 Al͑p , ␥͒ 28 Si nuclear reaction cross section curve at 404.9 keV, whose excitation curve and the resulting 27 Al profile are shown in Fig. 3͑a͒.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…3 4 using the narrow ͑⌫ =40 eV͒ resonance in the 27 Al͑p , ␥͒ 28 Si nuclear reaction cross section curve at 404.9 keV, whose excitation curve and the resulting 27 Al profile are shown in Fig. 3͑a͒.…”
Section: -mentioning
confidence: 99%
“…[3][4][5] A good tradeoff between the characteristics of these two materials 1, [6][7][8][9][10][11] can be achieved by forming ͑HfO 2 ͒ x ͑Al 2 O 3 ͒ 1−x mixed oxides, either homogeneous in composition or in nanolaminated structures. A convenient approach for depositing such films ͑oxides and mixed oxides͒ is the atomic layer deposition ͑ALD͒ technique, where self-saturating surface chemical reactions are employed.…”
mentioning
confidence: 99%
“…It is suggested that the amorphous Al 2 O 3 phase becomes metastable with respect to a crystalline alumina polymorph, due the nanometer size scale of the film/substrate combination. Since some of the uses for ALD Al 2 O 3 films include gate oxide for electronics, 3,4 protective barriers, 5 as well as potential coatings in energy materials, [6][7][8][9][10] it is critical to characterize these coatings on the nanoscale. For example, in the case of energy materials, there are recent reports of enhanced stability and extended cycling of Li-ion battery nanomaterials coated with ALD Al 2 O 3 thin films, [6][7][8][9][10] 9 This work assumes that the Al 2 O 3 coating is amorphous, as would be expected.…”
mentioning
confidence: 99%
“…5 The deposition of semiconductor device grade films of Al 2 O 3 and HfO 2 on Si is well established. 6,7 However, prior work on using noble metal nanoparticles to increase dielectric constants has focused primarily on polymer and glass dielectrics and processes that are not readily compatible with current integrated circuit fabrication. [8][9][10] Conversely, studies utilizing techniques similar to that used here have not focused explicitly on permittivity enhancement or dielectric properties.…”
mentioning
confidence: 99%